Impact of peripapillary staphylomas on the vascular and structural characteristics in myopic eyes: a propensity score matching analysis - Nie, Fen; Zhang, Lurong; Cao, Mengdan; Zhou, Dengming; Liu, Ke; Ouyang, Junyi; Luo, Lijia; Zhu, Ruiling; Liu, Shaosan; Duan, Xuanchu (Graefe's archive for clinical and experimental ophthalmology, 2023)
Purpose To apply propensity score matching to evaluate the impact of peripapillary staphylomas (PPS) on vascular and structural characteristics in the myopic eyes. Methods This was a prospective, cross-sectional study. Forty-one control eyes and 41 eyes with PPS were analyzed. The eyes were selected using propensity score matching analysis based on the age and axial length. All subjects underwent ophthalmologic examinations for assessing vessel and structure parameters using swept-source optical coherence tomography (SS-OCT), OCT angiography, color fundus photography, and ocular biometry. Results As compared with control eyes, the eyes with PPS had shallower anterior chamber depth (3.61 ± 0.24 mm vs 3.77 ± 0.24 mm, P = 0.004), higher intraocular pressure (IOP) (16.59 ± 2.88 mmHg vs 14.53 ± 2.45 mmHg, P = 0.002), and higher myopic spherical equivalent (− 11.52 ± 3.22D vs − 9.88 ± 2.20D, P = 0.009). while corneal curvature and lens thickness between the two groups were not statistically different. Compared with control eyes, increased macular deep vessel density, reduced macular choriocapillaris and radial peripapillary capillary, and thinning retinal layer, ganglion cell complex, choroidal layer as well as the superior and inferior peripapillary retinal nerve fiber layer were observed in eyes with PPS, apart from larger disc area, parapapillary atrophy area, and degree of disc rotation. Logistic regression analysis revealed that the IOP ( P = 0.046), disc rotation ( P = 0.003), and average peripapillary choroidal thickness ( P = 0.009) were associated with the presence of PPS. Conclusion Close association of PPS with exacerbation of myopia and anatomical alterations was observed which not only affected the eye posterior segment but also the anterior segments. We further identified significant reductions in the radial peripapillary capillary and macular choroidal perfusion with the increase in macular deep retinal flow blood of myopic eyes with PPS. Higher IOP, thinner peripapillary choroidal thickness, and rotated optic disc were risk factors for the presence of PPS.